Exploring the effect of digital finance on financial inclusion in Uganda, a reflection from Lira City - Eton, Marus; Mwosi, Fabian; Amandu, Ishaq Yassin; Ocan, Johnson; Ogwel, Bernard Patrick (Journal of Electronic Business & Digital Economics, 2025)
Purpose – The study aims to discuss financial inclusion (FI) as a facilitator of digital financing with intension of solving challenges relating to financial exclusion. Design/methodology/approach – Both descriptive and correlation research designs were used to understand the nexus between digital finance (DF) and FI. The study collected data from 300 respondents, which included vendors and dealers in agricultural produce, who were selected purposively and randomly. Findings – The study found a significant contribution of DF to FI and the variations in FI due to mobile money (MM) and Internet banking are significant. MM and smartphones are very often used in performing commercial transactions due to easy accessibility compared to ATMs, the Internet and agent banking, which is always restricted. Research limitations/implications – The study only focused on how DF platform affects financial inclusiveness in Lira City and did not explore other financial services. Social implications – The quickest and widest adoption of MM by rural communities is mostly a factor of user-friendliness, which seem to be lacking in other bank applications or products. Originality/value – The study offers a significant insight on challenges related to the financial inclusiveness, which is a global concern by many economies.